Agricultural production economics - Debertin, David L. (Collier Macmillan, 1986)
The format and coverage remains similar to the first edition, many small revisions and updates have been made. All graphs have been redrawn using the latest in computer imaging technology. The book contains a comprehensive treatment of the traditional agricultural production economics topics employing both detailed graphics and differential calculus. The text focuses on the neoclassical factor-product, factor-factor and product-product models, and is suitable for an advanced undergraduate or a beginning graduate-level course in static production economics. Chapters also deal with linear programming, risk and uncertainty and intertemporal resource allocation. A basic knowledge of differential calculus is assumed. Individual chapters are largely self-contained, and the book is suitable for instruction at a variety of levels depending on the specific needs of the instructor and the mathematics background of the students.